Effect of social support on illness perception in patients with atrial fibrillation during "Blanking Period": Mediating role of sense of mastery - Yun‐Mei Ding; Cui‐Ping Liu; Hong‐Xuan Xu; Mao‐Jing Wang; Jing‐Ya Zhang; Jia‐Yun Gu; Yan Cui; Lili Wei; Yan Zhang (Wiley, 2023)
Abstract Aim To explore whether sense of mastery can mediate the relationship between social support and illness perception in patients with atrial fibrillation (AF) who were at the "Blanking Period." Design A cross‐sectional design. Methods 405 patients with AF who were at the "Blanking Period" in the Affiliated Hospital of Qingdao University were recruited; they completed a set of questionnaires, including the Perceived Social Support Scale, the Personal Mastery Scale and the Brief Illness Perception Questionnaire. Results Social support and sense of mastery were both adversely connected to illness perception. The indirect effect of social support on illness perception through sense of mastery was negative, accounting for 86.04% of the total effect. Conclusion During the "Blanking Period," better social support and sense of mastery contribute to a positive illness perception of AF patients. Social support also can influence patients' illness perception indirectly via the mediator of sense of mastery.